2004
DOI: 10.1016/j.cell.2004.09.002
|View full text |Cite
|
Sign up to set email alerts
|

Mis16 and Mis18 Are Required for CENP-A Loading and Histone Deacetylation at Centromeres

Abstract: Centromeres contain specialized chromatin that includes the centromere-specific histone H3 variant, spCENP-A/Cnp1. Here we report identification of five fission yeast centromere proteins, Mis14-18. Mis14 is recruited to kinetochores independently of CENP-A, and, conversely, CENP-A does not require Mis14 to associate with centromeres. In contrast, Mis15, Mis16 (strong similarity with human RbAp48 and RbAp46), Mis17, and Mis18 are all part of the CENP-A recruitment pathway. Mis15 and Mis17 form an evolutionarily… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

42
624
2
2

Year Published

2005
2005
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 398 publications
(679 citation statements)
references
References 43 publications
(2 reference statements)
42
624
2
2
Order By: Relevance
“…Centromere localization limited to the period of chromosome segregation supports their role in spindle attachment. Taken together, the behavior of these groups was generally consistent with the subcomplex structures that have been identified from genetic interaction and biochemical purification studies (Hayashi et al, 2004;Obuse et al, 2004;Liu et al, 2005).…”
Section: Meiotic Behaviors Of Kinetochore Proteins Observed In Livingsupporting
confidence: 53%
See 3 more Smart Citations
“…Centromere localization limited to the period of chromosome segregation supports their role in spindle attachment. Taken together, the behavior of these groups was generally consistent with the subcomplex structures that have been identified from genetic interaction and biochemical purification studies (Hayashi et al, 2004;Obuse et al, 2004;Liu et al, 2005).…”
Section: Meiotic Behaviors Of Kinetochore Proteins Observed In Livingsupporting
confidence: 53%
“…Recently, it has been reported that S. pombe Moa1 functions in meiotic cohesin Rec8-mediated monopolar spindle attachment at meiosis I and that its centromere localization depends on Cnp3, a CENP-C homolog (Yokobayashi and Watanabe, 2005). In S. cerevisiae, centromere localization of meiotic cohesin Rec8 is reduced by loss of CHL4 (Marston et al, 2004), which is a homolog of S. pombe Mis15, and Mis15 requires Mis6 for its centromere localization (Hayashi et al, 2004). Mis6 is also required for loading of Cnp1, a CENP-A homolog (Takahashi et al, 2000).…”
Section: Mis6 Complex: Basic Architecture Of the Kinetochorementioning
confidence: 99%
See 2 more Smart Citations
“…Consistent with this hypothesis, RNA interference (RNAi) is required for the localization of many kinetochore proteins Oegema et al, 2001;Goshima et al, 2003). However, several kinetochore proteins do not seem to require CenH3 for localization, suggesting that CenH3-independent assembly pathways also exist (Goshima et al, 2003;Hayashi et al, 2004;Regnier et al, 2005). In addition, the overexpression of human CenH3 fails to nucleate complete kinetochore assembly, despite driving CenH3 localization to euchromatin (Van Hooser et al, 2001).…”
Section: Introductionmentioning
confidence: 72%